2013
DOI: 10.1016/j.biopsycho.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and induced cognitive fatigue: Effects on memory activation in healthy males

Abstract: a b s t r a c tWe investigated the relationship between individual differences in acute fatigue and endogenous cortisol changes elicited by the sustained performance of cognitively demanding tasks (fatigue condition). Healthy males provided salivary cortisol measurements and subjective fatigue ratings, and were scanned (functional magnetic resonance imaging) during memory encoding and recognition tasks in fatigue and control conditions. A group of 15 'responders' showed significantly higher cortisol levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Multiple sclerosis had increased awakening cortisol and decreased CARCruz [70]201543Breast cancerBFI and CFQMSC, DHEA-SNl MSC, Nl DHEA-SPts undergoing ChTx included anthracyclinesMarchand [31]20141043H/BMaslachDAC, CAR, SCR, NSC↑DAC, ↓CAR, ↑SCR, ↓NSCOnly BO; Groups of severe distress or depression not includedAggarwal [30]2014227HealthyCFQMSC, NSC, 0.25 mg DST, DHEA-SNl MSC, Nl NSC, Nl 0.25 mg DST, ↓DHEA-SEvaluation of chronic, widespread pain, chronic orofacial pain, chronic fatigue (but not CFS), irritable bowel syndromeTell D [71]2014130Breast cancerMFIDAC, CAR, SCR, NSC↓CAR, ↓SCR, ↑DAC, ↑NSCPost-surgery breast cancer, regardless of ChTx. Not adjusted to sleeping patternsWolfram [32]201353H/BMaslachMSC, 1 mcg CST, DST/CRH test (1.5 mg DST + 100 mcg CRH)Nl MSC, ↓post-1 mcg ACTH, Nl ACTH and cortisol DST-CRHHigh over-commitment present blunted serum and salivary cortisol and ACTH responses to DST-CRH testKlaassen [33]201327HealthyMP (Beck & Luine, 2010) and Stress Tasks (Wang, 2006)MSC, post-stressNl MSC, Nl post-stressA complex test sequence was performed but not reproducedEek [34]2012581HealthySOFI-20DAC, CAR, NSC, SCR, MSCNl DAC, Nl CAR, Nl NSC, Nl SCR, Nl MSCWomen: reduced awakening, increased CAR, increased SCR; Men: increased awakening and reduced CAR – when fatiguedSjors [35]2012247H/BDCSRD and SMBQDAC, 15 min CARNl DAC, Nl 15 min CARRahman [54]201130CFSPrevious Dx – No questionnaireMSC, SCR, NSCNl MSC, Nl SCR, Nl NSCMoya-Albiol [37]201064H/BMaslachDAC, CARNl DAC, Nl CARKumari [38]20094,299HealthySF-36DAC, CAR, NSC, SCR↓DAC, ↓CAR, ↑...…”
Section: Resultsmentioning
confidence: 99%
“…Multiple sclerosis had increased awakening cortisol and decreased CARCruz [70]201543Breast cancerBFI and CFQMSC, DHEA-SNl MSC, Nl DHEA-SPts undergoing ChTx included anthracyclinesMarchand [31]20141043H/BMaslachDAC, CAR, SCR, NSC↑DAC, ↓CAR, ↑SCR, ↓NSCOnly BO; Groups of severe distress or depression not includedAggarwal [30]2014227HealthyCFQMSC, NSC, 0.25 mg DST, DHEA-SNl MSC, Nl NSC, Nl 0.25 mg DST, ↓DHEA-SEvaluation of chronic, widespread pain, chronic orofacial pain, chronic fatigue (but not CFS), irritable bowel syndromeTell D [71]2014130Breast cancerMFIDAC, CAR, SCR, NSC↓CAR, ↓SCR, ↑DAC, ↑NSCPost-surgery breast cancer, regardless of ChTx. Not adjusted to sleeping patternsWolfram [32]201353H/BMaslachMSC, 1 mcg CST, DST/CRH test (1.5 mg DST + 100 mcg CRH)Nl MSC, ↓post-1 mcg ACTH, Nl ACTH and cortisol DST-CRHHigh over-commitment present blunted serum and salivary cortisol and ACTH responses to DST-CRH testKlaassen [33]201327HealthyMP (Beck & Luine, 2010) and Stress Tasks (Wang, 2006)MSC, post-stressNl MSC, Nl post-stressA complex test sequence was performed but not reproducedEek [34]2012581HealthySOFI-20DAC, CAR, NSC, SCR, MSCNl DAC, Nl CAR, Nl NSC, Nl SCR, Nl MSCWomen: reduced awakening, increased CAR, increased SCR; Men: increased awakening and reduced CAR – when fatiguedSjors [35]2012247H/BDCSRD and SMBQDAC, 15 min CARNl DAC, Nl 15 min CARRahman [54]201130CFSPrevious Dx – No questionnaireMSC, SCR, NSCNl MSC, Nl SCR, Nl NSCMoya-Albiol [37]201064H/BMaslachDAC, CARNl DAC, Nl CARKumari [38]20094,299HealthySF-36DAC, CAR, NSC, SCR↓DAC, ↓CAR, ↑...…”
Section: Resultsmentioning
confidence: 99%
“…These tasks highly rely on executive control, demanding additional mental effort, and are therefore expected to induce fatigue. A previous study has confirmed that this manipulation increases fatigue ratings in adults (Klaassen et al, 2013).…”
Section: Fatigue Manipulationmentioning
confidence: 58%
“…The fatigue-inducing manipulation consisted of 15 min of mental arithmetic followed by: 15 min of brainteaser puzzles (such as arithmetic sequences and syllogisms); 10 min of a computerized Stroop task (Stroop, 1935) adopted from Evers and colleagues (Evers, Van der Veen, Jolles, Deutz, & Schmitt, 2009) with extra auditory interference; and an N-back computer task (2-and 3-back) for another 20 min (see also Klaassen et al, 2013 for details). These tasks highly rely on executive control, demanding additional mental effort, and are therefore expected to induce fatigue.…”
Section: Fatigue Manipulationmentioning
confidence: 99%
“…In contrast, the opposite pattern was noted for CFS participants. Previous research indicates decreased activation of the hippocampus during a fatiguing test battery involving working memory and inhibitory function was linked to HPA-axis dysfunction and greater fatigue ratings (Klaassen et al, 2013). Aberrant activation of the hippocampus during extended PASAT performance in patients with CFS has also been noted (Cook et al, 2007).…”
Section: Differences In Dynamic Fc Between Groupsmentioning
confidence: 99%